ARCHITECTURAL FEATURES OF HYDROTHERAPY FACILITIES IN THE ARCHITECTURE OF THE COUNTRIES OF THE MIDDLE EAST AND CENTRAL ASIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article dedicated to architecture of bath-house and Hospital buildings in traditional architecture of Eeurt. The article considered the development of this type buildings from ancient time to the beginning of XX sentry.